Pendidikan Sastra Berbasis Multikultural di Era Society 5.0 - Siti Nur Afifatul Hikmah (PT FORMOSA CENDEKIA GLOBAL, 2022)
The flow of globalization is seen as a big wave that brings impact and changes in various aspects of life. This includes changes in life from the industrial era 4.0 to the era of society 5.0. Through multicultural-based literary education, the public can be more open to understanding and appreciating the diversity that exists in Indonesia. Therefore, through literary works such as novels, short stories, poetry, and dramas, they can provide knowledge about multicultural-based literary education. The purpose of this study was to determine the form of multicultural-based literary education in the era of society 5.0 and the utilization of regional cultural potential as a multicultural-based literary learning in the era of society 5.0. This research method uses a qualitative approach with the type of case study. Researchers used data collection techniques in this study in the form of data or information adapted to real phenomena and facts.